Description of a new genus and new species of deep-water stenopodid shrimp from the western Atlantic, with remarks on Odontozona Holthuis, 1946 and Richardina A. Milne-Edwards, 1881 (Decapoda: Stenopodidea) - Anker, Arthur (Zootaxa, 2023)
A new genus, Jogoya, gen. nov., is established for a new species of stenopodid shrimp, Jogoya alucia sp. nov., the holotype and single specimen of which was collected during a manned submersible dive in the Bahamas in 2019, and two additional specimens collected during earlier expeditions, one also from the Bahamas and one from Anguilla. The new genus appears to occupy an intermediate position between Richardina A. Milne-Edwards, 1881 and Odontozona Holthuis, 1946. Jogoya gen. nov. is characterised by the presence of unusually large spines on the cervical cincture of the carapace, a feature shared with a species originally described as Odontozona foresti Hendrickx, 2002 and herein tentatively transferred to Jogoya gen. nov., as Jogoya foresti (Hendrickx, 2002), comb. nov. The most conspicuous morphological difference between J. alucia sp. nov. and J. foresti is in the armature of the posterior half of the carapace, with the latter species having a post-cervical cincture armed with strong spines, which is absent in the new species. The two species of Jogoya gen. nov. also differ greatly by their colour patterns.